RASO BANAGARI: EKSPRESI SOSIAL PERANTAU TERHADAP PEMBANGUNAN KAMPUNG HALAMAN - Syamsurizaldi, Syamsurizaldi; Putri, Annisa Aulia; Sari, Miftahul Viona; Yoliandri, Ridho (JSW (Jurnal Sosiologi Walisongo), 2020)
Generally, emigrants have a deep interest in the condition of their hometown. In the Minang community, that sense is called "raso banagari", a sense of belonging to the nagari. One form of embodiments of raso banagari is to participate in the development of nagari, both directly and indirectly. Managing the participation of nagari emigrants in the Solok Regency, the Solok Regent made policy in the form of Regent Regulation Number 10 of 2017 concerning Collaboration between the Regional Government and the Nagari Government with Solok Emigrants. Solok Regency has 47 nagari emigrant organizations out of 70 nagari(s). This study aims to determine and analyze the form and level of emigrant participation in nagari development in Solok Regency. This research uses a combination of quantitative and qualitative methods. The results showed that the form of emigrant participation in the development of the nagari was mostly in the form of donations of money, ideas, and networking.